Development of A Learning Model Based on RME for Improving Mathematical Literacy Skills and Students’ Mathematical Disposition - Lubis, Erwina Rahmawati; Fauzi, KMS. Muhammad Amin; Mulyono, Mulyono (Jurnal Paedagogy, 2024)
This study aims to develop of a learning model based on Realistic Mathematics Education (RME) that are valid, practical, and effective to improve mathematical literacy skills and students’ mathematical disposition. This study uses a research and development method with modified Plomp model. This research was carried out at SMP Negeri 9 Medan in the odd semester of the 2023/2024 academic year. The instruments in this study were the Mathematical Literacy Ability Test and the Mathematical Disposition Questionnaire. The data analysis technique in this study used descriptive statistical analysis. The results of this research showed that: (1) the RME-based learning model developed met the criteria for validity, practicality and effectiveness of the learning model; (2) increasing students’ mathematical literacy skills using the realistic RME-based learning model developed in terms of the N-Gain in trial I of 0.29 with low criteria and in trial II of 0.59 with medium criteria. (3) increasing students’ mathematical disposition abilities using the developed RME learning model in terms of the average in trial I and trial II, namely 5.04.